Recasting anthropological knowledge : - Edwards, Jeanette 1954-; Petrovic-Steger, Maja (Cambridge University Press, 2011)
"The authors of the chapters presented in this collection take various strategies and we take our lead from them. Their brief was to pick up, run with, and depart from key Strathernian concepts by way of their own current research. The result is something more stable than such metaphors of flight suggest. Instead of running, the authors of these chapters have decided to dwell. Debbora Battaglia (beginning this volume), for example, remarking on the generosity with which Strathern cites her students and colleagues and on how she reworks and re-worlds their ethnographic accounts, shows what it might mean to accompany rather than depart from Strathern: in her words, to go a-worlding with her. Adam Reed (ending this volume) is more cautious: for him, it is a moot point whether Stratherns generosity in citing her students is evidence of her having been inspired by them: but, dwelling on the concept of inspiration itself, Reed reveals its unbidden, all- encompassing, dynamic and deeply social and sociable nature. Multiple flows of inspiration run through the various chapters in this volume and not only between Strathern and her students"-- Provided by publisher. innovative and multifaceted reflection on the impact and inspiration of the scholarship of eminent anthropologist Marilyn Strathern. A distinguished team of international contributors, all former students of Strathern, reflect on the impact of their relationship with their teacher and address the wider conceptual contribution of her work through their own writings. The essays provide an accessible entry into Stratherns scholarship for those new to her work and a rich source of material which mobilises and deploys her concepts, including new ethnographic examples and discussion of contemporary political issues, for those more familiar with her scholarship. The result is a collection that dissects, contextualises and reroutes concepts of relationality, inspiration and knowledge in novel and unpredictable ways. Recasting Anthropological Knowledge will prove invaluable to all students of anthropology and will be of interest to scholars across the social sciences"-- Provided by publisher.